Maslinic Acid Attenuates Ischemia/Reperfusion-Induced Acute Kidney Injury by Suppressing Inflammation and Apoptosis Through Inhibiting NF-κB and MAPK Signaling Pathway - Sun, Wenjuan; Choi, Hong Sang; Kim, Chang Seong; Bae, Eun Hui; Ma, Seong Kwon; Kim, Soo Wan (Frontiers in Pharmacology, 2022)
Inflammation and apoptosis are the major contributors to the mechanisms of acute kidney injury (AKI) due to renal ischemia-reperfusion injury (IRI). Maslinic acid (MA), a pentacyclic triterpene acid widely found in dietary plants. The current study was to demonstrate the renoprotective effect of MA on IRI-induced AKI, and to investigate the role of inflammation and apoptosis related signaling pathways as a molecular mechanism. C57BL/6J mice were subjected to IRI 72 h and MA was daily administered by intraperitoneal injection during this period. In parallel, rat renal proximal tubule cells (NRK52E) were prophylactically treated with MA and then were exposed to hydrogen peroxide (H2O2). MA treatment significantly inhibited the mRNA expression of interleukin (IL-1β), tumor necrosis factor-α (TGF-α), monocyte chemoattractant protein-1 (MCP-1), and intercellular adhesion molecule-1(ICAM-1). Also, MA reduced expression of Bax/Bcl2 ratio and cleaved caspase-3. In NRK52 cells, MA inhibited the IκBα degradation, blocked NF-κB/p65 phosphorylation and nuclear translocation. The phosphorylation of ERK, JNK and p38 was attenuated by MA in IRI-induced kidney injury and H2O2 stimulated NRK52 cells. The expression levels of IL-1β, MCP-1 and ICAM-1 was upregulated in H2O2 stimulated NRK52E cells, which was attenuated by NF-κB inhibitor. H2O2 treatment increased Bax/Bcl2 ratio and cleaved caspase-3 in NRK52E cells, which was counteracted by MAPK inhibitors. Together our data demonstrate that MA suppresses IR-induced AKI injury through NF-κB and MAPK signaling pathways and MA is a promising agent in the treatment of kidney diseases.